Tele-eye care models during COVID-19 pandemic: A systematic review - Ramya K Kharvi; Soujanya Padmashali; Suchithra Poojary; Siddharth K Karthikeyan; Pooja Nandagopal; Malathi Acharya (TNOA Journal of Ophthalmic Science and Research, 2020)
Coronavirus disease 2019 (COVID-19) pandemic has affected eye care practices in several ways. To reach out to people who need eye care services during this pandemic, eye care practitioners started tele-eye care (TEC) practice worldwide. This review aims to describe the methods, including protocols, regulations of TEC, and its usefulness during the COVID-19 pandemic. Articles relevant to the aim were searched from various databases such as “PubMed, Scopus, Wiley Online Library, ProQuest, CINAHL, and Web of Science.” The last date of the search was June 16, 2020. Retrieved articles underwent screening process against the predefined inclusion and exclusion criteria, and the irrelevant articles were excluded. Data extraction was done using excel sheets. Quality assessment and risk of bias were assessed. The results of the included articles were summarized and tabulated. A total of 188 articles were retrieved from database screening, of which only two articles met the inclusion criteria. Results of the included studies reported that TEC practice was favorable to patients in saving their time, money, and was easy to use. Patients would like to continue TEC practices in future as an alternative to an in-person consultation. TEC practice mainly benefited people in rural areas and people living far from the hospital. The percentage of patients utilizing TEC practice has been increasing.